Primary Squamous Cell Carcinoma of the Urinary Bladder Presenting as Peritoneal Carcinomatosis - Beltran, Himisha (Hindawi Publishing Corporation, 2010)
We report an unusual case of a 78-year-old Caucasian female, who presented with peritoneal carcinomatosis and hypercalcemia, and was found to have a rapidly progressive primary squamous cell carcinoma of the urinary bladder. Squamous cell bladder carcinoma is a rare malignancy in the United States, accounting for just 1–3% of bladder tumors. Interestingly our patient lacked the established risk factors, including exposure to the parasite Schistosoma haematobium, recurrent urinary tract infections, bladder calculi, radiation exposure, chronic indwelling catheter, neurogenic bladder, or tobacco abuse. Although hypercalcemia has been rarely described, an initial presentation of peritioneal carcinomatosis has not been previously reported.